Dietary fibre requirements of feedlot lambs - Smith, Pieter Schalk (University of the Free State, 2008)
No abstract available
Keywords: Fiber in animal nutrition; Sheep -- Feed utilization efficiency; Sheep -- Feeding and feeds; Dissertation (M.Sc.Agric. (Animal, Wildlife and Grassland Sciences))--University of the Free State, 2008